How to improve the potential of microalgal biostimulants for abiotic stress mitigation in plants? - Vangenechten, Bram; De Coninck, Barbara; Ceusters, Johan (Frontiers in Plant Science, 2025)
Abiotic stress is among the most critical factors limiting crop productivity worldwide and its importance is further exacerbated by climate change. In recent years, microalgal biostimulants have gained attention for their potential to enhance plant resilience towards abiotic stress. However, significant hurdles still persist, particularly regarding the unknown modes of action of microalgal biostimulants, which is a concern for stringent regulatory requirements and product reliability. The aim of this review is to improve the potential of microalgal biostimulants for abiotic stress mitigation in plants by addressing different key parameters shaping the efficacy of microalgal biostimulants, encompassing cultivation approaches, extraction techniques, and application methods. Furthermore, it also highlights how microalgal biostimulants modulate plant morphology, physiology and biochemistry under drought, salinity, and heat stress—three predominant stressors anticipated to intensify under climate change. Notably, these biostimulants consistently enhance drought stress tolerance by improving biomass accumulation, nutrient uptake, and water use efficiency through enhanced photosynthesis and stomatal regulation. These effects are largely driven by the accumulation of osmoprotectants and antioxidant compounds. In contrast, salt stress mitigation is highly species-dependent, with some microalgae enhancing stress tolerance through osmoprotectant and antioxidant accumulation, while others reduce these compounds, potentially lowering stress perception via unknown mechanisms. Despite the significance of the abiotic stress, heat stress mitigation by microalgal biostimulants remains an underexplored research area. Additionally, indirect applications of microalgae—ranging from biotechnological innovations to desalination—underscore the broader potential of these organisms in agricultural resilience. Collectively, this review identifies three key gaps in the existing literature—the diversity gap, the practical gap, and the research gap—while outlining promising avenues for future research in microalgal biostimulant development.